Stakeholder Collaboration in Managing Student Behavior and School Discipline: A Cambodian Primary School Case Study - Hai Sophan (SUJANA: Education and Learning Review, 2026)
Improving student behavior and maintaining school discipline remain central concerns for educational administrators, teachers, and policymakers in Cambodia, where schools navigate the competing pressures of cultural tradition, limited resources, and evolving community expectations. This study employed a qualitative phenomenological approach to generate descriptive and interpretive insight into how parents, school principals, teachers, and other institutional actors perceive and enact school discipline policies at the primary school level. Data were collected through structured in-depth interviews and open-ended questionnaires, with audio recordings and verbatim transcripts produced for all interview sessions. A total of 48 participants were selected through purposive sampling, comprising five school directors, five vice-directors, five librarians, 20 classroom teachers, four parents, two Buddhist monks, one non-governmental organization volunteer, and one representative each from the Ministry of Education Youth and Sport, a provincial department of education, and a district office of education, drawn from both public and private primary schools in Cambodia. Thematic analysis of the data identified four dimensions of student behavior, two domains of institutional disciplinary practice, and six categories of stakeholder involvement. Schools that demonstrated stronger coordination among stakeholders reported fewer students requiring formal disciplinary intervention. Four principal challenge clusters were identified, encompassing family disengagement, teacher capacity limitations, peer influence, and external cultural pressures. The findings underscore the need for adaptive, morally grounded, and collaboratively governed disciplinary frameworks that respond to the growing complexity of primary school environments in Cambodia.